THE EVOLUTION OF DOME- AND SHEAR-TYPE STRUCTURAL FEATURES OF NORTHWESTERN ONEGA AREA (KARELIYA ROCK MASSIF) - Kolodyazhnyi S.Yu.; Zykov D.S.; Leonov M.G.; Orlov S.Yu. (My University, 2000)
The authors of this paper discuss the specific geological structure and structural evolution of dome- and shear-type structural features in the region northwest of the Onega Lake. These structural features are associated, in space and genesis, with the broad and extensive zones of shear-type tectonic flow, surrounding the Paleo-Proterozoic Onega Synclinorium. Based on the lithostructural, structural-paragenetic, and radio-isotope data, the sheer zones of this region are interpreted as long-lived, inherited structural features which developed at the background of the periodical successions of transgression and transtension conditions and changes in the directions of shear faults from the Archean to the recent time. The early Proterozoic time witnessed the formation in these structural features of periodically remobilized dome-shear structural features, the traces of which were preserved as Paleoproterozoic chaotic block breccias and syn-sedimentation structural features, (1830-1670 Ma), and as Riphean (1270 Ma, ?) and neotectonic morphostructural manifestations. The formation of the domal shear structural features was associated with transgression, that is, with the volumetric shear deformations at the background of the general compression, which involved, simultaneously, the rocks of the metamorphic basement and sedimentary cover. The squeezing mechanisms, operating simultaneously with various shear deformations, caused the formation of subisometric dome-shaped structural features, occurring as echelon structural features.
Keywords: GEOLOGICAL STRUCTURE; STRUCTURAL EVOLUTION; ONEGA AREA; BRECCIAS; PALEO-PROTEROZOIC ONEGA SYNCLINORIUM; Precambrian::Proterozoic; Докембрий::Протерозой